EVALUATION OF ANTI DIABETIC POTENTIAL OF CRUDE ETHANOLIC EXTRACT OF CINNAMONUM VERUM - B, Keerthana.; R, Gayathri .; Priya, V.Vishnu (International Journal of Psychosocial Rehabilitation, 2020)
To evaluate the anti diabetic potential of crude ethanolic extract of CINNAMONUM verum. This sample was purchased from the organic super market and then it is made as a powder. Then the ethanolic extract was prepared. And then the anti diabetic potential of this compound is estimated. It is evident that CINNAMONUM verum posses the anti diabetic potential that is the crude ethanolic extract of this compound posses. As of now it is used as a spice, in future it can be used on the daily basis to prevent the diabetes As we can prevent diabetes nowadays, by using this compound we can create awareness among people.